2014
DOI: 10.1063/1.4896999
|View full text |Cite
|
Sign up to set email alerts
|

Decay dynamics of α,β-carboxylic methyl esters (CH3OCOCH:CHR) in the lower-lying excited states—Resonance Raman and complete active space self-consistent field calculation study

Abstract: The photophysics of two α,β-carboxylic methyl esters after excitation to the light absorbing S2(ππ(*)) state were studied by using the resonance Raman spectroscopy and complete active space self-consistent field (CASSCF) method calculations. The vibrational spectra were assigned on the basis of the experimental measurements and the B3LYP/6-31G(d) computations, as well as the normal mode analysis. The A-band resonance Raman spectra of methyl 2,4-pentadienoate (M24PDA) and methyl trans cronoate (MTCA) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…We thus speculate that the very high efficiency of the S 2 (ππ*) → S 0 internal conversion for thymine in water is mostly due to the predominant wave‐packets motion towards the S 2 (ππ*)/S 0 in the Franck–Condon region. In contrast, the very strong CO stretch mode of uracil in water indicates that there is no noticeable out‐of‐plane distortion motion of the CCCO motif occurs in the Franck–Condon region, and the initial wave‐packets shall move mostly towards the S 2,min (ππ*) or S 2 (ππ*)/S 1 CI, if keep in mind that the structure of S 2,min (ππ*) or S 2 (ππ*)/S 1 CI for uracil is nearly planar, as is similar to the short‐time structural dynamics and the planar S 2 (ππ*)/S 1 CI structures of MTCA and 3M3P2O, and that both the S 2 (ππ*) → S 0 and the 1 ππ* → nπ* → S 0 paths are equally important (~50% for each) for uracil …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…We thus speculate that the very high efficiency of the S 2 (ππ*) → S 0 internal conversion for thymine in water is mostly due to the predominant wave‐packets motion towards the S 2 (ππ*)/S 0 in the Franck–Condon region. In contrast, the very strong CO stretch mode of uracil in water indicates that there is no noticeable out‐of‐plane distortion motion of the CCCO motif occurs in the Franck–Condon region, and the initial wave‐packets shall move mostly towards the S 2,min (ππ*) or S 2 (ππ*)/S 1 CI, if keep in mind that the structure of S 2,min (ππ*) or S 2 (ππ*)/S 1 CI for uracil is nearly planar, as is similar to the short‐time structural dynamics and the planar S 2 (ππ*)/S 1 CI structures of MTCA and 3M3P2O, and that both the S 2 (ππ*) → S 0 and the 1 ππ* → nπ* → S 0 paths are equally important (~50% for each) for uracil …”
Section: Resultsmentioning
confidence: 88%
“…The most important difference lies in the disappearance of the CO stretch mode for thymine and M24PDA, and the appearance of the strong CO stretch mode for uracil, MTCA and 3M3P2O. To our understanding, the disappearance of the CO stretch mode of thymine in water or M24PDA is mostly due to the out‐of‐plane distortion motion of the CCCO motif occurring suddenly in the Franck–Condon region, if keep in mind that the structure of S 2 (ππ*)/S 0 CI for thymine or S 2 (ππ*)/S 1 CI for M24PDA is severely distorted and that the S 2 (ππ*) → S 0 internal conversion via S 2 (ππ*)/S 0 CI is the predominant channel (~90% population) for thymine. We thus speculate that the very high efficiency of the S 2 (ππ*) → S 0 internal conversion for thymine in water is mostly due to the predominant wave‐packets motion towards the S 2 (ππ*)/S 0 in the Franck–Condon region.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is found that when the ab initio calculated resonance Raman intensities deviate greatly from the experimental values, the mixing of two states in the FC region is generally involved. More specifically, when abnormally intense experimental resonance Raman intensities appear in the non‐totally symmetric fundamental modes, they generally result from overtones and combination bands with the totally symmetric fundamental modes; therefore, a curve‐crossing or conical intersection must exist between the relevant excited states . In this case, Herzberg–Teller vibronic‐coupling theory and CASSCF calculations are used to determine the exact coupling states and the associated geometric structures of the curve‐crossing or conical intersection points.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, Herzberg–Teller vibronic‐coupling theory and CASSCF calculations are used to determine the exact coupling states and the associated geometric structures of the curve‐crossing or conical intersection points. For example, the nonadiabatic decay mechanisms of α,β‐enones and α,β‐carboxylic methyl esters in the light‐absorbing 1 ππ* states were studied recently by the above technique, and the corresponding nonadiabatic decay channel initiated from S 2,FC (ππ*) to S 1 (nπ*) via the S 2 (ππ*)/S 1 (nπ*) curve‐crossing point was revealed.…”
Section: Introductionmentioning
confidence: 99%